2020
DOI: 10.2183/pjab.96.024
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater oxygen anomaly related to the 2016 Kumamoto earthquake in Southwest Japan

Abstract: Here, we report the groundwater oxygen isotope anomalies caused by the 2016 Kumamoto earthquake (M JMA 7.3) that occurred in Southwest Japan on April 16, 2016. One hundred and seventeen groundwater samples were collected from a deep well located 3 km to the southeast of the epicenter in Mifune Town, Kumamoto Prefecture; they were drinking water packed in PET bottles and distributed in the area between April 2015 and March 2018. Further, the oxygen and hydrogen isotopes were evaluated via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…The mechanism for changes in the chemical compositions of subsurface water bodies can be attributed to several processes: 1) water-rock interactions; 2) the mixing of groundwater and formation or pore waters; 3) by the mixing of different reservoirs with different chemical compositions; 4) by the mixing of meteoric waters; 5) artificial pollutants (Igarashi et al, 1995;Song et al, 2006;Reddy et al, 2011;Skelton et al, 2014;Sano et al, 2020). The processes (1) and (2) may gradually cause the hydro-chemical changes during a long period of time, resulting in a shift from an equilibrium between water and rock because of increased exposure of reactive surfaces to the fluid.…”
Section: Mechanism For Geochemical Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for changes in the chemical compositions of subsurface water bodies can be attributed to several processes: 1) water-rock interactions; 2) the mixing of groundwater and formation or pore waters; 3) by the mixing of different reservoirs with different chemical compositions; 4) by the mixing of meteoric waters; 5) artificial pollutants (Igarashi et al, 1995;Song et al, 2006;Reddy et al, 2011;Skelton et al, 2014;Sano et al, 2020). The processes (1) and (2) may gradually cause the hydro-chemical changes during a long period of time, resulting in a shift from an equilibrium between water and rock because of increased exposure of reactive surfaces to the fluid.…”
Section: Mechanism For Geochemical Changesmentioning
confidence: 99%
“…Song et al (2003) collected commercially bottled groundwater around the epicenter for investigating changes in groundwater composition and found the obvious increase of SO 4 2and NO 3 − concentrations before the Chi-Chi earthquake. Similarly, Sano et al (2020) reported oxygen isotope anomalies before the Kumamoto earthquake by analyzing groundwater samples from the packaged drinking bottle collected from a deep well located 3 km to the epicenter. Yang et al (2006) have continuously monitored the gas composition of the Chunglun (CL) mud pool along the Chukou Fault (CKF), and proposed CO 2 /CH 4 variations in bubbling gases were sensitive to the earthquake events.…”
Section: Introductionmentioning
confidence: 99%